Rancang Bangun Sistem Pendeteksi Kebocoran Gas Elpiji Berbasis Internet Of Things Menggunakan Esp32 - Rudi Hermawan; Mudjianto Mudjianto (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2026)
Liquefied Petroleum Gas (LPG) is one of the most widely used energy sources in households and small industries. However, gas leakage often becomes a major cause of fires and explosions due to delayed detection. Therefore, an early warning system capable of detecting LPG leaks in real time is required. This research aims to design and implement an Internet of Things (IoT)-based LPG gas leak detection system using the ESP32 microcontroller. The system utilizes the MQ-2 gas sensor to detect LPG concentration in the surrounding environment. When the detected gas concentration exceeds the specified threshold, the system activates a buzzer alarm, displays warning information on an Android smartphone, and sends monitoring data through the internet. The research method employed is the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance. System testing was carried out using the Black Box Testing method to verify the functionality of each component. The results indicate that the developed system successfully detects LPG gas leakage, provides early warning notifications, and performs real-time monitoring through smartphone devices. This system is expected to improve household safety and minimize fire hazards caused by LPG gas leaks.